2014
DOI: 10.1007/s40140-014-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Current Use of Noninvasive Hemoglobin Monitoring in Anesthesia

Abstract: Modern technology enables clinicians to assess hemoglobin levels noninvasively and continuously. Some instruments also provide concentrations of other types of hemoglobin, such as methemoglobin and carboxyhemoglobin. Such information obtained immediately and noninvasively can be helpful in the management of critically ill patients or those undergoing surgery with bleeding. However, the accuracy of noninvasive hemoglobin measurements should be evaluated before clinical application, particularly for transfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Others exclusion criteria included vascular surgery, pediatric surgery, hemodynamically unstable patients, and those admitted following major trauma with blood loss, missing data, and hepatic and jaundiced patients. Elective general and orthopedic surgery were only included to avoid the reported effects of specific types of surgery on the SpHb values [12,15].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others exclusion criteria included vascular surgery, pediatric surgery, hemodynamically unstable patients, and those admitted following major trauma with blood loss, missing data, and hepatic and jaundiced patients. Elective general and orthopedic surgery were only included to avoid the reported effects of specific types of surgery on the SpHb values [12,15].…”
Section: Patientsmentioning
confidence: 99%
“…This diversity between various researchers motivated our team to design this current research to study the Masimo Radical-7 performance as a non-invasive hemoglobin monitor. This device utilizes multiple wavelengths of light (500-1300 nm) to measure the fractional hemoglobin and calculate the total hemoglobin concentration [12,13]. The primary aim of this study was to measure the non-invasive SpHb (g/dL) among adults prior to surgery and to investigate SpHb correlation and agreement with laboratory hemoglobin (Hb, g/dl), which was measured within 24 h of planned anesthesia and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Radical-7 manufacturer, the PI value has a definite influence on SpHb accuracy and obtaining SpHb values, and a PI ! 1.4% was recommended (Lee et al 2014). To assess the influence of the PI, in the present study the PI values were used to separate the SpHb pairs of data into two groups (PI < 1% group and PI !…”
Section: Discussionmentioning
confidence: 99%
“…Coquin et al [8] investigated the accuracy in critically ill patients with gastrointestinal bleeding, and found that the number of unavailable measurements associated with inadequate perfusion index values was significantly higher in patients with noradrenaline administration (42% versus 15%, P < 0.05). In addition, as Lee et al [30] indicated in the recent review, the presence of peripheral vascular disorders can affect the accuracy of NIHb measurement. Thus, vasopressor administration and other causes of decreased peripheral perfusion can lead to an inadequate accuracy of NIHb monitoring.…”
Section: Peripheral Perfusionmentioning
confidence: 98%